Evaluating the real-world safety of cholestyramine for the treatment of hyperlipidemia: disproportionality analysis of FAERS data - Li, Qiang; Fan, Mengmeng; Gao, Anbang; Qin, Limin (Frontiers in Medicine, 2026)
BackgroundHypercholesterolemia is a significant risk factor for severe cardiovascular diseases. Cholestyramine lowers serum low-density lipoprotein cholesterol (LDL-C) levels and is clinically indicated for the treatment of primary hypercholesterolemia, relieve itching symptoms caused by bile acid accumulation in cholestatic diseases (such as primary biliary cirrhosis), as well as to manage bile acid diarrhea resulting from bile acid metabolic disorders. With its widespread clinical application, it is essential to understand its safety in real-world settings.MethodsThis study evaluated the clinical safety of cholestyramine by analyzing all adverse event reports since 2004 in the FDA Adverse Event Reporting System (FAERS), where cholestyramine was identified as the primary suspected drug. Bayesian Confidence Propagation Neural Network (BCPNN), the Medicines and Healthcare Products Regulatory Agency (MHRA) composite criteria method, Multi-Item Gamma Poisson Shrinker (MGPS), Proportional Reporting Ratio (PRR), and Reporting Odds Ratio (ROR) were used to analyze adverse events associated with cholestyramine.ResultsThe study results confirmed known adverse reactions of cholestyramine, such as constipation, abdominal discomfort, bloating, steatorrhea, bleeding tendencies, night blindness, hyperchloremic acidosis, osteoporosis, rashes, and local irritation caused by deficiencies in vitamins K, A, and D, which are also listed in the drug’s package insert. Additionally, adverse reactions not documented in the package insert were identified, including off-label use, administration for unapproved indications, gastroesophageal reflux disease (GERD), irritable bowel syndrome (IBS), fecal abnormalities (color changes, softening, hardening), blood glucose fluctuations, tooth fracture, and exacerbation of concurrent medical conditions. This study also underscores the importance of early detection of adverse reactions associated with cholestyramine.ConclusionBy providing insights into both known and potential adverse reactionsin real-world settings, the findings offer enhanced safety information to assist clinicians in prescribing cholestyramine for conditions such as hypercholesterolemia, cholestasis-associated pruritus, and bile acid diarrhea.